The polarity protein Scrib mediates epidermal development and exerts a tumor suppressive function during skin carcinogenesis - Pearson, H.; McGlinn, E.; Phesse, T.; Schluter, H.; Srikumar, A.; Godde, N.; Woelwer, C.; Ryan, A.; Phillips, W.; Ernst, M.; Kaur, Pritinder; Humbert, P. (BioMed Central Ltd., 2015)
Background: The establishment and maintenance of polarity is vital for embryonic development and loss of polarity is a frequent characteristic of epithelial cancers, however the underlying molecular mechanisms remain unclear. Here, we identify a novel role for the polarity protein Scrib as a mediator of epidermal permeability barrier acquisition, skeletal morphogenesis, and as a potent tumor suppressor in cutaneous carcinogenesis. Methods: To explore the role of Scrib during epidermal development, we compared the permeability of toluidine blue dye in wild-type, Scrib heterozygous and Scrib KO embryonic epidermis at E16.5, E17.5 and E18.5. Mouse embryos were stained with alcian blue and alizarin red for skeletal analysis. To establish whether Scrib plays a tumor suppressive role during skin tumorigenesis and/or progression, we evaluated an autochthonous mouse model of skin carcinogenesis in the context of Scrib loss. We utilised Cre-LoxP technology to conditionally deplete Scrib in adult epidermis, since Scrib KO embryos are neonatal lethal. Results: We establish that Scrib perturbs keratinocyte maturation during embryonic development, causing impaired epidermal barrier formation, and that Scrib is required for skeletal morphogenesis in mice. Analysis of conditional transgenic mice deficient for Scrib specifically within the epidermis revealed no skin pathologies, indicating that Scrib is dispensable for normal adult epidermal homeostasis. Nevertheless, bi-allelic loss of Scrib significantly enhanced tumor multiplicity and progression in an autochthonous model of epidermal carcinogenesis in vivo, demonstrating Scrib is an epidermal tumor suppressor. Mechanistically, we show that apoptosis is the critical effector of Scrib tumor suppressor activity during skin carcinogenesis and provide new insight into the function of polarity proteins during DNA damage repair. Conclusions: For the first time, we provide genetic evidence of a unique link between skin carcinogenesis and loss of the epithelial polarity regulator Scrib, emphasizing that Scrib exerts a wide-spread tumor suppressive function in epithelia.